2001
DOI: 10.1002/rrr.657
|View full text |Cite
|
Sign up to set email alerts
|

Bank profile and structure as determinants of macroinvertebrate assemblages—seasonal changes and management

Abstract: Management and restoration procedures in rivers frequently have a major influence on the bank and marginal zone, depending on the timing of disturbance and the eventual structure of the bank. This study examines changes in macroinvertebrate communities in four different bank types at 3-weekly intervals throughout a year. The banks differed in their profile and in their structure: shallow sloping and vegetated, stepped shallow profile, steep profile (eroded soil bank), and iron revetments. Velocity patterns ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 30 publications
(36 reference statements)
1
16
1
1
Order By: Relevance
“…The importance of livestock poaching on LIFE score is also not surprising: its influence on invertebrates has been documented elsewhere (Naura and Robinson, 1998;Armitage et al, 2001). In lowland streams, the locations of poaching can be highly localized, although downstream impacts through increased silt loading would be evident.…”
Section: Discussionmentioning
confidence: 91%
“…The importance of livestock poaching on LIFE score is also not surprising: its influence on invertebrates has been documented elsewhere (Naura and Robinson, 1998;Armitage et al, 2001). In lowland streams, the locations of poaching can be highly localized, although downstream impacts through increased silt loading would be evident.…”
Section: Discussionmentioning
confidence: 91%
“…Although there are no specific data available on seasonal changes in faunal and floral diversity for ditches in the area, studies of emergent bankside communities on the Frome (Armitage et al, 2001) suggest that biodiversity is highest in the period August/September, an observation supported by work in ditches in the Netherlands . A total of 16 sites was therefore sampled along its length in September 1998.…”
Section: Study Area and Methodsmentioning
confidence: 93%
“…The River Frome adjacent to the ditch has been the subject of some recent intensive work on freshwater macroinvertebrate communities (Armitage et al, 1995(Armitage et al, , 2001Cannan and Armitage, 1999) These studies undertaken at the same time of year (September/October) provide the opportunity to compare the contribution of instream, bankside and ditch communities with the biodiversity of the floodplain. In most cases, the sample unit is the 15 s sweep and after standardization for identification level (Chironomidae to sub-family and tribe level) the results are comparable.…”
Section: Contribution To Biodiversitymentioning
confidence: 99%
“…Aquatic vegetation provides substratum for invertebrates and zooplankton (Carpenter and Lodge, 1986). In correspondence with this, Armitage et al (2001) observed a three times higher number of macroinvertebrate taxa and a five to six times higher total abundance of taxa in shallow vegetated riparian sites compared with the steeply sloped and artificial banks. Bats prefer bank side plants and avoid water bodies with no vegetation edge (Russ and Montgomery, 2002).…”
Section: Introductionmentioning
confidence: 66%